Sweet Pluronic poly(propylene oxide)-b-oligosaccharide block copolymer systems: Toward sub-4 nm thin-film nanopattern resolution. (5th July 2020) - Mumtaz, Muhammad; Takagi, Yasuko; Mamiya, Hiroaki; Tajima, Kenji; Bouilhac, Cécile; Isono, Takuya; Satoh, Toshifumi; Borsali, Redouane
Graphical abstract: Thin films made from the self-assembly of carbohydrate-based block copolymers Highlights: High χ carbohydrate block copolymers self-assemble into sub-4 nm nanopatterns. Nanofeature depends on their composition and annealing conditions. Order-to-order transition occurred under high-temperature solvent vapors. Carbohydrate-containing PPOs can advantageously replace classical Pluronic systems. Abstract: Block copolymers (BCPs) with a high Flory–Huggins interaction parameter ( χ ) are promising alternatives to conventional nanopatterning materials for future nanolithography and nanotechnology applications. Herein, we described AB- and ABA-type BCPs comprising oligosaccharides (maltoheptaose, maltotriose, and maltose as the A block) and poly(propylene oxide) (PPO, as the B block) as new high- χ BCP systems, which can be termed "Sweet Pluronics". The BCPs were successfully synthesized by click reaction between azido-functionalized PPO and propargyl-functionalized maltooligosaccharides. These BCPs undergo microphase separation in bulk state to provide various nanopatterns, i.e., sub-4 nm nanofeatures (cylinders, lamellae, and spheres) with domain spacing as low as 6.2 nm, depending on their composition and the applied annealing conditions. The thin film of these BCPs fabricated on a silicon substrate also showed various microphase-separated structures. When the BCP thin films were subjected to high-temperature solvent vapor annealing using a µ-wave oven as the heating source, their morphologies changed from parallel lamellar to cylindrical because of the preferential swelling of PPO. Overall, these results confirmed that the present "Sweet Pluronics" system is promising high- χ materials for sub-4 nm nanopatterning applications.